Relationship between Haemoglobin A1c and Short Term Outcome in Patients with ST-elevation Myocardial Infraction (STEMI) (Bangladesh Heart Journal, 2016)
Introduction: Every year, 17.1 million lives are claimed by the global burden of cardiovascular disease (CVD), 82% of which are in the developing world. Glycated hemoglobin (HbA1c), even at levels considered in the normal range, emerged as an independently significant predictor of heart-disease events, stroke, and death over more than a decade.Methodology: After applying the inclusion and exclusion criteria, 113 patients with ST segment elevation myocardial infarction were enrolled in this study after taking informed written consent from the patient or attending guardian. Follow up was done during hospital stay for mortality, arrhythmia, cardiogenic shock, cardiac arrest, congestive heart failure, mechanical complication (eg ventricular septum rupture, wall rupture), left ventricular systolic dysfunction, stroke etc.Result: The median age of patients was 53.4 years (range 22 to 85 years), patients with an HbA1c >6.5% were slightly older than those with HbA1c 6.5%. Patients with elevated HbA1c had more LVSD (54%) (p=0.022), heart failure (81%) (p= < .001). However, patients with HbA1c >6.5% were more likely to have cardiogenic shock as an outcome but it is not statistically significant (p= .528), whereas cardiac arrest, arrythmia and mechanical complication were more among HbA1c 6.5) haemoglobin A1c level.Bangladesh Heart Journal 2015; 30(1) : 29-32